Macrofinance Modeling from Asset Allocation Perspective - Kollár, Miroslav; Jílek, Josef, 1957-; Holman, Robert, 1953-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
The dissertation dealt with the interaction between the macro-economy and financial markets. In the first part of the dissertation I laid down a general case for macro-based active asset allocation. In the main part of my dissertation, after a theoretical introduction to term structure models and macrofinance models, I developed a VAR macrofinance model of the term structure of interest rates for the Czech economy based on the dynamic interpretation of the Nelson-Siegel model, and showed the use of such modeling framework in bond-yield prediction and asset allocation.
Vedoucí práce: Josef Jílek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: obecná ekonomická teorie a dějiny ekonomických teorií [obor disert. práce]; disertace; dissertations